Evaluation of Information Technology Governance at XYZ Bondowoso Hospital Using COBIT 2019 and ITIL V4 - Ari Cahaya Puspitaningrum; Heri Supriyanto; Mohammad Al Hafidz; Mochamad Nurhadi; Nabilla Rizky Ananda (Teknika)
This study is in the field of information technology (IT) governance. Researchers investigated the implementation of IS/IT in a hospital located in Bondowoso, East Java. The results of the investigation showed that the hospital had implemented IS/IT by general hospital regulations and government policies. However, the IT governance system there is not good; there has been no evaluation process. Thus, the purpose of this study is to evaluate IT governance to determine the quality of their IT services and provide recommendations for improvement. The framework used is COBIT 2019 and ITIL V4. Data collection was carried out by interviewing and distributing questionnaires. Data were analyzed using a design toolkit that includes 10 design factors in COBIT 2019. The results of this study are that 3 management practices must achieve capability targets at level 4, namely BAI02, BAI03, and BAI07. Based on the current conditions, BAI02 and BAI03 have achieved level 3, and BAI07 has achieved level 2, with largely achieved rating criteria. This indicates that there is a gap. This study provides recommendations for actions that need to be taken by hospitals that focus on these 3 management practices. Recommendations are made with reference to COBIT 2019 and ITIL V4.